"Salía de uno y me metí en otro1": Exploring the Migration-Violence Nexus Among Central American Women. (May 2019) - Cook Heffron, Laurie
Increasing numbers of Central American women cross the U.S.–Mexico border, prompting social service providers, advocates, and policy makers to investigate motivations and appropriate responses. Drawing from a constructivist grounded theory study and in-depth qualitative interviews, this article explores women's experiences of domestic and sexual violence in relation to migration. Findings reveal interconnections across multiple and interconnecting categories of violence as precipitating factors for migration, during border-crossing, and following arrival in the United States. This study fills gaps in our understanding of the violence-migration nexus and provides direction for policy, practice, and advocacy, in the context of shifting political landscapes and migration trends.